Happiness in the dual society of urban China:Hukou identity, horizontal inequality and heterogeneous reference - Shiqing Jiang; Ming Lu; Hiroshi Sato (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2008)
This paper studies the impact of income inequality on the subjective well-being of different social groups in urban China. We classify urban social groups according to their hukou status: rural migrants, 'born?urban residents, and 'acquired?urban residents who once changed their hukou identity from rural to urban. We focus on how the horizontal inequality-income disparity between migrants and urban residents-affects individual happiness. The main results are as follows. First, migrants suffer from unhappiness when the horizontal inequality increases, but urban residents show a much smaller aversion to the horizontal inequality. Second, migrants will not be happier if their relative incomes within their migrant group increase, while urban residents do become happier when their incomes increase within their group's income distribution. Third, 'acquired?urban residents have traits of both migrants and 'born?urban residents. They have an aversion to the horizontal inequality like migrants, and they also favor higher relative income among urban residents. Fourth, 'born?urban residents have lower happiness scores when they are old. People who are Communist Party members strongly dislike the horizontal inequality. Our findings suggest that migrants, 'acquired?urban residents, elderly people and Party members from 'born?urban residents are the potential proponents of social integration policies in urban China.
Keywords: I31; O15; R23; 330; Horizontal inequality; Happiness; Hukou identity; Migration; Social integration; horizontal inequality; happiness; Houku identity; migration; social integration